History of Sexual Assault Perpetration and Violence-Related Prosocial Tendencies Among Men by Fraternity Affiliation Status. (July 2022) - Hoxmeier, Jill C.; Zapp, Daniel
The purpose of this cross-sectional study was to examine self-reported sexual assault perpetration history, as well as violence prevention-related prosocial tendencies, among fraternity men, unaffiliated men with membership intentions, and unaffiliated men without membership intentions with data from 262, 634 college men in the United States. Results indicate that fraternity status was related to sexual assault perpetration, both prior to and while at their current institution of higher education; both perpetration history and fraternity status significantly related to diminished violence prevention-related prosocial tendencies. The findings have important implications for future research and practice to reduce the incidents of sexual assault on college campuses.